2002
DOI: 10.1080/00000000000000007
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of venous resection for ductal adenocarcinoma of the pancreatic head

Abstract: There is no reason to exclude patients with suspected venous infiltration from radical pancreaticoduodenectomy including venous resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
76
0
3

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(89 citation statements)
references
References 14 publications
10
76
0
3
Order By: Relevance
“…[12][13][14][15]17,[27][28][29][30] This higher rate of postoperative complications did not translate into an increased length of hospital stay; overall, we found no significant difference in mortality between patients with and without VR, which is in agreement with most of the previous literature. 12,14,15,17,[28][29][30][31] Only 1 previous study, in which no difference in overall in-hospital mortality was found, reported higher 30-day mortality among patients who underwent concomitant VR. 27 A recent systematic review and meta-analysis, focused only on arterial resections, also found increased mortality rates among patients who underwent VR compared with pancreatectomy alone.…”
Section: Commentsupporting
confidence: 82%
“…[12][13][14][15]17,[27][28][29][30] This higher rate of postoperative complications did not translate into an increased length of hospital stay; overall, we found no significant difference in mortality between patients with and without VR, which is in agreement with most of the previous literature. 12,14,15,17,[28][29][30][31] Only 1 previous study, in which no difference in overall in-hospital mortality was found, reported higher 30-day mortality among patients who underwent concomitant VR. 27 A recent systematic review and meta-analysis, focused only on arterial resections, also found increased mortality rates among patients who underwent VR compared with pancreatectomy alone.…”
Section: Commentsupporting
confidence: 82%
“…Hartel et al, examined outcomes between their cohort of patients (n=271) who underwent pancreaticoduodenectomy +/− major vein resection. Their analysis revealed no difference in the rates of perioperative morbidity, mortality, and 5-year survival between the two groups [14]. Similar results were observed by Tseng et al, at MD Anderson Cancer Center for their patients who underwent pancreaticoduodenectomy with major vascular resection.…”
Section: Extended Pancreaticoduodenectomy With Major Vascular Resectionsupporting
confidence: 73%
“…In this report, the operation performed depended on the location of the tumor within the pancreas, and included pylorus-preserving pancreaticoduodenectomy, classic Whipple pancreaticoduodenectomy, total pancreatectomy, distal pancreatectomy, and subtotal pancreatectomy. Traditionally, as with pancreatic adenocarcinoma, PNET vascular involvement was considered a contraindication to resection, however based on the experience previously reviewed regarding adenocarcinoma [14,15,17], resection of these locally advanced, and even metastatic tumors was undertaken. Of the patients described above, 4 had PV or SMV involvement and all received complete resection of their tumor with vascular reconstruction by vein patch, vein graft, or synthetic graft.…”
Section: Radical Resections For Pancreatic Neuroendocrine Tumorsmentioning
confidence: 99%
“…There are no prospective randomized trials comparing pancreatectomy with and without VnR. Most retrospective studies demonstrate that while VnR is associated with longer operative times and larger blood loss, the morbidity and mortality of pancreatectomy with VnR is similar to those of pancreatectomy alone (Table 3) [42][43][44][45][46][47][48][49][50][51][52][53][54]. There was a high incidence of venous invasion (50%-82%) among patients who underwent VnR.…”
Section: Portal/mesenteric Vascular Resectionmentioning
confidence: 99%